Social Integration of Indonesian Ahmadiyya Community to Preserve Existence in Jambi, 2003–2013 - Totok Suhadak; Singgih Tri Sulistiyono; Yety Rochwulaningsih (Diponegoro University, 2021)
This study focuses on the social integration of Ahmadiyya Indonesia Community (JAI) to maintaine its Existence in Jambi in the period 2003-2013. The issue raised in this study is the ability of the JAI in Jambi to maintain its existence at a time when Ahmadiyya congregations JAI in several regions in Indonesia suffered tragic fates after their places of worship were vandalized and their members suffered acts of violence perpetrated by local residents. In this regard, this article will answer the questions of why and how JAI Jambi carried out social integration efforts in order to maintain its existence. Issues that were subject of this study are the growth of JAI in Jambi from 2003-2013 and the social integration of JAI in Jambi to maintain its existence.